Dead Sea media : orality, textuality and memory in the scrolls from the Judean desert - Miller, Shem, 1974- (Studies on the Texts of the Desert of Judah, 2019)
In Dead Sea Media Shem Miller offers a groundbreaking media criticism of the Dead Sea Scrolls. Although past studies have underappreciated the crucial roles of orality and memory in the social setting of the Dead Sea Scrolls, Miller convincingly demonstrates that oral performance, oral tradition, and oral transmission were vital components of everyday life in the communities associated with the Scrolls. In addition to being literary documents, the Dead Sea Scrolls were also records of both scribal and cultural memories, as well as oral traditions and oral performance. An examination of the Scrolls' textuality reveals the oral and mnemonic background of several scribal practices and literary characteristics reflected in the Scrolls.